Youth Entrepreneurship in Visegrad Countries - Marian Holienka; Anna Pilková; Zuzana Jančovičová (Entrepreneurial Business and Economics Review)
Objective: The aim of our paper is to analyse the entrepreneurial activity drivers of youth and young adults in Visegrad countries, considering the opportunity/necessity motivation dichotomy.